(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article examines the role of the President of Kazakhstan N. Nazarbayev to the people of Kazakhstan and the consolidation of the importance of his ideas «Kazakh Eli». Largely thanks to the fruitful work of the Leader of the Nation in the area of national policy, a unique type of Kazakh model of interethnic and interreligious harmony, the special atmosphere of trust, solidarity and mutual understanding, when every citizen, regardless of ethnic or religious affi liation, and has enjoyed the fullness of human rights and freedoms guaranteed by the Constitution. Keywords: head of the State, Kazakhstan nation, national policy, inter-ethnic harmony, national development.